2020
DOI: 10.3389/fpsyt.2020.00397
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Intervention Targeting Autobiographical Memory Impairment in Patients With Schizophrenia Using a Wearable Camera: A Proof-of-Concept Study

Abstract: Autobiographical memory (AM) impairment in schizophrenia affects the richness of detail in personal memories and is one of the major predictors of patients' social functioning. Despite the empirical evidence attributing these difficulties to a defective encoding process, cognitive remediation interventions targeting AM in schizophrenia often focus on the remote past, making it difficult to address the consequences of poor encoding. Our study evaluated the efficacy of an innovative approach using a wearable cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
(115 reference statements)
1
8
0
Order By: Relevance
“…For instance, teaching participants encoding strategies enhancing binding has been shown to reduce memory deficit in clinical populations by at encoding (Corrêa et al, 2015). The use of new technologies, such as wearable cameras (Allé et al, 2017;Silva et al, 2013), also have the potential to strengthen re-encoding of autobiographical events via exposure to the photographs taken by the device (Woodberry et al, 2015) and may therefore be especially useful for patients with schizophrenia (Dassing et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, teaching participants encoding strategies enhancing binding has been shown to reduce memory deficit in clinical populations by at encoding (Corrêa et al, 2015). The use of new technologies, such as wearable cameras (Allé et al, 2017;Silva et al, 2013), also have the potential to strengthen re-encoding of autobiographical events via exposure to the photographs taken by the device (Woodberry et al, 2015) and may therefore be especially useful for patients with schizophrenia (Dassing et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In all clinical studies enrolled in this review, lifelogging was found to have beneficial effects on the subjective and objective measurements of memory. All case studies on diverse brain-damaged samples (Berry et al, 2007(Berry et al, , 2009Brindley et al, 2011;Browne et al, 2011;Loveday & Conway, 2011;Pauly-Takacs et al, 2011;Svanberg & Evans, 2014), and also all group studies on patients with Alzheimer's dementia (Crete-Nishihata et al, 2012;Dassing et al, 2020;Woodberry et al, 2015) concluded that lifelogging is beneficial in rehabilitation of memory. In healthy samples, this finding was not always supported.…”
Section: Discussionmentioning
confidence: 99%
“…, used a bigger group of patients (51) and concluded that using Sensecam is more effective for memory rehabilitation compared to a number of other techniques. The clinical study by Dassing et al (2020) enrolled 17 patients diagnosed with chronic schizophrenia and concomitant memory disorders as well 15 healthy controls. The researchers employed a Narrative Clip for their study and concluded that using the device can improve memory of amnesic patients.…”
Section: Clinical Group Studiesmentioning
confidence: 99%
See 2 more Smart Citations